The Efficacy of the Office of the Data Protection Commissioner in Safeguarding the Right to Privacy in Kenya: An Empirical Review - Kimwaki, Benedict Mutnda (Eastasouth Institute, 2025)
This paper critically examines the operational environment of the Office of the Data Protection Commissioner in Kenya with the objective of identifying challenges and proposing recommendations to enhance its efficacy. By delving into these complexities, the study aims to offer insights that can inform improvements, thereby fostering a more robust data protection framework in the country. Ultimately, the paper seeks to bridge the gap between desired levels of protection and the current state of personal data security, ensuring that legal provisions translate into practical safeguards amidst the evolving digital landscape. The paper focuses on desk review approach and analyses statutes, regulations, case law and other legal writings which have informed the assertions in regard to office of data protection commissioner and its role in safeguarding the right to privacy. From the review, it has been concluded that the establishment of the Office of the Data Protection Commissioner was an critical move towards promoting and enhancing the right to privacy in the country, putting Kenya in a good position as key leading countries across the globe that have gone a notch high in promoting the right to privacy. As part of recommendations, the paper has recommended the essence of continuous improvement as this would enable the office of data protection commission to keep pace with the ever-changing technological world particularly on data security and privacy.